2016
DOI: 10.1128/aem.01363-16
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High-Pressure Treatment on Spores of Clostridium Species

Abstract: This work analyzes the high-pressure (HP) germination of spores of the food-borne pathogen Clostridium perfringens (with inner membrane [IM] germinant receptors [GRs]) and the opportunistic pathogen Clostridium difficile (with no IM GRs), which has growing implications as an emerging food safety threat. In contrast to those of spores of Bacillus species, mechanisms of HP germination of clostridial spores have not been well studied. HP treatments trigger Bacillus spore germination through spores' IM GRs at ϳ150… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 51 publications
1
35
0
Order By: Relevance
“…However, with spores of at least Clostridioides difficile , CaDPA release does not trigger completion of spore germination, although the CaDPA‐less spores have a higher core water content and are less wet heat resistant than dormant spores (Doona et al . 2016; Setlow et al . 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, with spores of at least Clostridioides difficile , CaDPA release does not trigger completion of spore germination, although the CaDPA‐less spores have a higher core water content and are less wet heat resistant than dormant spores (Doona et al . 2016; Setlow et al . 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Under these conditions the main inactivation force is the temperature (Reineke et al., ; Sevenich et al., ). Recently, the differences in germination under pressure between Clostridium spores and Bacillus spores have been revealed, showing interesting insights (Figure ; Doona et al., ; Lenz & Vogel, ; Paredes‐Sabja, Setlow, & Sarker, ). In Bacillus spp ., DPA release triggers cortex lytic enzyme (CLE) activation; CLE action is not essential for DPA release, but it can accelerate it.…”
Section: State Of the Artmentioning
confidence: 99%
“…In Clostridium difficile or Clostridium perfringens Doona et al. () observed that the inactivation mechanism differs in comparison to Bacillus species. For the tested strains the initiation of cortex hydrolysis by SleC precedes and triggers DPA release.…”
Section: State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, they reported that heating of food to temperatures above 85 C would be necessary to inactivate viable spores of C. difficile. More recently, Redondo-Solano, Burson, and Thippareddi (2016) reported much higher thermal resistance for three hypervirulent and one nonvirulent strains of C. difficile spores ranging from 22.14 h at 70 C to 4.93 min at 70 to 90 C. Microwave heating (Malyshev, Williams, Lees, Baillie, & Porch, 2019;Ojha et al, 2016), high pressure treatment (Doona et al, 2016), and use of electrolyzed water (Tkhawkho, Jackson, Nitzan, & Peretz, 2017) have also been proposed for destruction of C. difficile spores.…”
mentioning
confidence: 99%